ENHANCING MILLENNIAL PERFORMANCE THROUGH INDIVIDUAL CHARACTERISTICS AND EMPLOYEE ENGAGEMENT - Ilhami, Susanti Dwi; Armanu, Armanu; Noermijati, Noermijati; Korsakul, Nattharuja (Jurnal Aplikasi Manajemen, 2021)
This study presents a model linking individual characteristics, employee engagement, and employee performance. The primary objective was to investigate the direct effect of individual characteristics on employee performance and its indirect effect through employee engagement. This study used a non-probability sampling technique with a saturation sampling type. The data were obtained by a questionnaire from a sample of 118 respondents of millennial employees in the media and information technologies sector in Yogyakarta. Data were analyzed by used variance-based SEM (SEM-PLS) and found four significant paths models. The result reveals that individual characteristics have a positive and significant effect on improving employee performance. Moreover, individual characteristics are significantly positive in increasing employee engagement, while employee engagement has a positive and significant effect on employee performance. The mediation test result indicated that employee engagement could partially mediate the relationship of individual characteristics on employee performance. Further research can incorporate variables that influence millennial performance, such as job characteristics, intention to leave, job satisfaction, and other variables to improve strategies in enhancing millennial performance.